2018
DOI: 10.1111/jre.12611
|View full text |Cite
|
Sign up to set email alerts
|

R‐spondin 2 promotes osteoblastic differentiation of immature human periodontal ligament cells through the Wnt/β‐catenin signaling pathway

Abstract: Objective: In this study, we measured the expression of R-spondin 2 (RSPO2) in periodontal ligament (PDL) tissue and cells. Further, we examined the effects of RSPO2 on osteoblastic differentiation of immature human PDL cells (HPDLCs). Background: R-spondin (RSPO) family proteins are secreted glycoproteins that play important roles in embryonic development and tissue homeostasis through activation of the Wnt/β-catenin signaling pathway. RSPO2, a member of the RSPO family, has been reported to enhance osteogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…(92,93) Addition of RSPO2 to an undifferentiated human PDL cell line expressing LGR4 induces more robust osteogenesis, although it is still unproven as this is mediated through a RSPO-LGR interaction. (89) An LGR-mediated mechanism may be accelerating osteogenic differentiation of tooth-associated progenitor cells, similar to in vitro results seen in studies with bone marrowderived cells and established cell lines. (65,66)…”
Section: Lgrs In Skeletal Remodelingsupporting
confidence: 59%
See 2 more Smart Citations
“…(92,93) Addition of RSPO2 to an undifferentiated human PDL cell line expressing LGR4 induces more robust osteogenesis, although it is still unproven as this is mediated through a RSPO-LGR interaction. (89) An LGR-mediated mechanism may be accelerating osteogenic differentiation of tooth-associated progenitor cells, similar to in vitro results seen in studies with bone marrowderived cells and established cell lines. (65,66)…”
Section: Lgrs In Skeletal Remodelingsupporting
confidence: 59%
“…(85)(86)(87)(88) Expression of LGR4 in particular was reported in an immature human PDL cell line (2 to 14 cells). (89) Under orthodontic strain in a rat model, LGR5 expression in vivo localizes with Runx2+ cells, specifically in the periapical region of the PDL during tooth movement and alveolar bone remodeling under the influence of these cyclic strain techniques. (90) Further,…”
Section: Lgrs In Skeletal Remodelingmentioning
confidence: 97%
See 1 more Smart Citation
“…Among which, its functional contribution to lncRNAs‐mediated cancer development has attracted people's attention 28. Through researches of numerous years, it was confirmed that enhanced nuclear translocation of β‐catenin indicates the activation of Wnt/β‐catenin pathway 29. The transcription factor SOX9 has been reported to activate Wnt/β‐catenin pathway in non‐small‐cell lung cancer 19.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that R-spondin proteins contribute to the regulation of tissue patterning and differentiation (Zhou et al, 2012;Storm et al, 2016;Zhu et al, 2016). Rspo2 has been reported to have the capacity of promoting osteoblast differentiation within MC3T3 E1 cells (Friedman et al, 2009;Zhu et al, 2016), mouse bone marrow stem cells (Knight et al, 2018), and human periodontal ligament cells (Arima et al, 2019) by modulating Wnt/β-catenin signaling. Bone marrow stem cells (BMSCs) isolated from Rspo2 Ftl mice (deficient in Rspo2) showed reduced osteogenesis compared with BMSCs from wild-type litter mates (Knight et al, 2018).…”
Section: Introductionmentioning
confidence: 99%